Extreme flood intensification in the Pearl River Basin in the future under 1.5° C, 2.0° C, and higher global warming levels - Qi, Wei; Huang, Ruiting; Cai, Yanpeng; Tan, Qian (Frontiers in Water, 2025)
The Pearl River Basin (PRB) is a vital economic hub in China, and sustains agriculture, industry, and regional water security for over 80 million people. While prior research has focused narrowly on flood frequency, flood impacts, or localized risk reduction, comprehensive assessments of extreme floods under critical global warming thresholds (1.5° C, 2.0° C and beyond) remain unexplored in PRB. Employing the WEB-DHM-SG model driven by ISIMIP3b bias-adjusted climate projections, this study analyzed extreme flood changes throughout the Pearl River Basin under incremental global warming levels from 1.5° C to 4.5° C (0.5° C intervals) for SSP126, SSP370, and SSP585 scenarios. Results show that, relative to the historical baseline (1985–2014), extreme floods across the PRB increase by 44–50% during the near future (2036–2065) and 57–68% in the far future (2071–2100), with the most pronounced escalations under higher emissions (SSP585). Sub-basin analyses reveal spatial heterogeneity in the timing and degree of increase. For example, at Boluo Station (Dongjiang sub-basin), extreme floods exhibit a biphasic response, declining initially then rising sharply by the far future. At Gaoyao Station (Xijiang sub-basin), extreme floods show a near-monotonic increase, with a slight reduction under SSP585. In contrast, at Shijiao Station (Beijiang sub-basin), extreme floods display a consistent upward trend across all scenarios. Furthermore, each 0.5° C increment of global warming significantly amplifies discharge, especially at Xijiang (largest absolute increase) and Dongjiang (highest relative increase, 7% per 0.5° C). These differential responses highlight the critical need for tailored adaptation measures, particularly infrastructure enhancements in the more sensitive Xijiang and Dongjiang sub-basins.